Surgical Case Reports - Inomata, Masafumi; Baba, Hideo; Otsuka, Masayuki; Miyagawa, Shigeru; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Surgical Case Reports has ended its publishing partnership with SpringerOpen as of 31 December 2024. For information on continued publicaiton of Surgical Case Reports from 2025 and new submission system, please visit new publisher website. SpringerOpen will continue to host an archive of all articles previously published in the journal and all articles published during its time with SpringerOpen (2015-2024) will remain fully searchable via SpringerOpen website.
Keywords: Surgery; Surgery